المجتمع المدني والسياسة: تحديات الانفصال والاتصال - إبراهيم, عمر الخير (Gezira Journal of Economic and Social Sciences; مجلد 13 عدد 2 (2022), 2022)
The paper aimed to examine the nature of the relationship between civil society and politics and its results; Positively or negatively, while taking Sudan context as a model for the study. The study adopted two main methods; historical approach that focuses on tracking civil society backgrounds and its development alongside with the analytical approach that helped to understand civil society emergence and development in general as well as in the Sudan context in particular. Though there are some people believe that relationship between them is subject to practice and not theory, there are clear indications that confirm the existence of a theoretical perception that describes the relationship and distinguishes its boundaries. The results confirmed that civil society is a social entity par excellence, it should not be involved in politics or in partisan activities, perhaps by virtue of its roles in the fields of civic education, awareness and advocacy for rights and developmental issues, it has an impact on political actors’ positions, but definitely, it is not a political entity or a political actor. The results of the study also concluded that the history of the relationship between civil society and politics in the Sudanese context has been characterized by tension and conflict at times, suppression and subordination at many times. Accordingly, the study concluded that civil society should be independent from politics, in order to enhance its social role and protect the society’s cohesion and unity.